Recurrence of Ischemic Stroke Patients with Common Risk Factors - kanti Dey , Subash; Bakshi, Lipy; ahmed, Anis; Md Shahidullah, -; Habib, Ahsan; Chowdhury, Ashish; Islam, Md Rafiqul (Bangladesh Journal of Neuroscience, 2019)
Background: Mortality and morbidity due to recurrent ischemic stroke is gradually increasing in Bangladesh due to gradual increase of life expectancy. Previously many studies were done to identify the risk factors of ischemic stroke. But there was scanty data about risk factors of recurrent ischemic stroke. So,it is time demanding to find out those risk factors for ischemic stroke recurrence to reduce the mortality and morbidity from recurrent ischemic stroke. The objective of the study was to determine the frequency of recurrence ischemic stroke events within one year of follow up after discharge from hospital admitted due to first ever stroke. Methods: This is a prospective cohort study. This study was conducted on 150 patients admitted in Neurology ward of BSMMU, presenting with first ever ischemic stroke. Patients mRS were evaluated three monthly interval for one year. Sudden onset mRS deterioration than previous one during this one year period was categorized as recurrence. Results: Stroke recurrence was found in 30 patients including 8 patients who died due to stroke recurrence. the most frequent age group was > 75 years representing 44.4% who developed recurrence of stroke The cumulative risk of recurrence rate was 14.7% at three months, 15.3% at six months, 17.3% at ninth months,20% at one year. Old age, Male sex, Hypertension, DM and dyslipidemia were the most common risk factors among recurrent stroke patients. Conclusion: It was concluded that in hospital admitted patients of first ever stroke, recurrence events was more in patients of older male patients with multiple risk factors.First three months was the worst period for recurrence after index stroke. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 33-38